2018
DOI: 10.12688/f1000research.15753.1
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection and progressive differentiation of effector-memory T cells

Abstract: Primary cytomegalovirus (CMV) infection leads to strong innate and adaptive immune responses against the virus, which prevents serious disease. However, CMV infection can cause serious morbidity and mortality in individuals who are immunocompromised. The adaptive immune response to CMV is characterized by large populations of effector-memory (EM) T cells that are maintained lifelong, a process termed memory inflation. Recent findings indicate that infection with CMV leads to continuous differentiation of CMV-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…And this is accompanied by an increase of HCMV-specific cells that re-express CD45RA [11] and express KLRG1 [47]. Moreover, using new computational tools, it was recently shown that inflationary MCMV-specific T cells are progressively differentiating in time (based on the markers KLRG1, CD44, CD27 and CD62L), long after the initial infection [74, 85]. In line with these studies is the observation that telomeres of HCMV-specific CD8 T cells are significantly shorter compared to the corresponding phenotypic subsets of the total CD8 T-cell pool [86].…”
Section: Establishment Of the Advanced Differentiation Phenotypementioning
confidence: 99%
“…And this is accompanied by an increase of HCMV-specific cells that re-express CD45RA [11] and express KLRG1 [47]. Moreover, using new computational tools, it was recently shown that inflationary MCMV-specific T cells are progressively differentiating in time (based on the markers KLRG1, CD44, CD27 and CD62L), long after the initial infection [74, 85]. In line with these studies is the observation that telomeres of HCMV-specific CD8 T cells are significantly shorter compared to the corresponding phenotypic subsets of the total CD8 T-cell pool [86].…”
Section: Establishment Of the Advanced Differentiation Phenotypementioning
confidence: 99%
“…But this population is on average significantly larger in CKD patients and may comprise over 50% of all circulating CD4 T cells [47]. Remarkably not all CMV seropositive individuals have such an expansion of CD4CD28 negative T cells, which is likely related to the initial infectious dose and the number of CMV reactivations [51,[59][60][61][62]. The total number of CD8 T cells is less affected by ageing, as the decline in naïve CD8 T cells is compensated by an expansion of highly differentiated memory T cells.…”
Section: Renal Failure and Adaptive Immunitymentioning
confidence: 99%
“…As previously described, MCMV replication in most organs is initially controlled in the course of the first week while specific T cell are primed. After antigen clearance, virus-specific memory Vaccines 2019, 7, 152 9 of 28 T cells are preserved and, in contrast to naïve T cells, rapidly respond upon re-encounter with a cognate antigen through direct effector functions or further proliferation and differentiation into a more advanced phenotype [115]. Memory subsets have been categorized, according to their functions, location, migration abilities and maintenance requirements into central memory T cells (TCM), effector memory T cells (TEM), tissue-resident memory T cells (TRM) and peripheral memory cells (TPM) [116].…”
Section: Cellular Response-t Cellsmentioning
confidence: 99%
“…Besides the well-described typical pattern of expansion and contraction of antigen-specific T cells, CMV infection is characterized by memory inflation [8], a virus-specific T cell response with skewed specificity that continues to expand during viral persistence [9,117]. This "inflationary" population is represented by circulating TEM (CD62L − ) which in contrast to TCM (CD62L + ) have a phenotype compatible with recent antigen activation that is believed to be induced by low level viral persistence through sporadic reactivation events [96,115]. Unlike other persistent infections such as HIV, hepatitis C virus (HCV) and hepatitis B virus (HBV), CMV infection leads to the production of fully functional, virus-specific T cells without any hallmarks of immune exhaustion [118,119].…”
Section: Cellular Response-t Cellsmentioning
confidence: 99%